DEVELOPMENT OF COORDINATION BETWEEN HEARING AND VOICE IN SINGING: REVIEW OF METHODICAL LITERATURE IN THE LATVIAN LANGUAGE - Ivane, Madara; Trīnīte, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of the study is to examine the reflection of the processes of formation of musicality, musical hearing and vocal skills in methodological materials published in Latvia. The aim of the study is to analyse the existing methodological materials from 21st century that deal with the development of children’s musical hearing as described by various authors. The study focuses on the primary school age, pre-mutation period children who, in addition to general education, are learning singing in vocational or interest education during individual or group lessons (ensembles and choirs). The research method used is the selection and summarization of opinions and recommendations of teachers of music subject, singing teachers and conductors in the work with children – soloists and choir singers, who are gaining their first skills in singing and intonative hearing, as described in various literature sources. The results of the study show that all of the examined materials conceptually coincide, but often different terminology and explanation of techniques is used, which does not always reveal the nature of each expression and technique, thus preventing the theoretically expressed knowledge from being put into practice. Many explanations are based on the empirical work by the authors of the source. There is a lack of methodological techniques that are based on scientifically proven facts.